Hubungan antara Kecerdasan Emosional dan Spiritualitas: Kajian Literatur Psikologi Islam - Ramilah Suta; Dwi Aristawidya R.; Khairiah Rawita; Adissah Putri Herdianti; Cristin Cristin; Rahmadianti Aulia (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Emotional intelligence (EQ) and spirituality (SQ) are two important aspects in shaping an individual's psychological balance. The study conducted a systematic review of 20 scientific articles to explore the relationship between the two in various contexts, such as education, organization, and health. The results of the study show that EQ and SQ are not only significantly interconnected, but also play a joint role in improving emotional regulation, resilience, and meaning of life. These findings confirm the importance of a holistic approach to self-development that integrates emotional and spiritual dimensions to achieve wholesome well-being. Further, empirical evidence indicates that individuals with high EQ and SQ tend to have better interpersonal skills, stronger adaptability, as well as lower levels of stress. The integration of these two constructs is also relevant for the design of positive psychology-based interventions and character education, as it can strengthen self-awareness, empathy, and value orientation. Thus, simultaneously strengthening EQ and SQ has the potential to be an effective strategy in improving quality of life and mental health across settings.